Response of yearling steers to burning, fertilization, and intensive early season stocking of bluestem pasture - Woolfolk, J.S.; Harbers, L.H.; Schalles, R.R.; Allen, Leland James; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Four hundred ninety-two acres of native bluestem range were divided into nine pastures for summer grazing by yearling steers. Five pastures were burned April 28; four were not burned. Burned and not burned pastures were treated with 0, 40, or 80 lbs. of nitrogen per acre applied aerially as granular urea. Stocking rates were determined from previous work on herbage production from experimental plots under similar treatments. Both average daily gains and weight gains per acre were greater from each burned treatment than from not burned treatments with similar fertilization and stocking rate. Steers grazing an early-season-stocked pasture intensively for 76 days produced the highest average daily gain of 1.72 lbs. highest gains per acre (137 lbs.) were on the burned pasture that received 80 lbs. of nitrogen per acre.
Keywords: Beef; Steers; Fertilization; Bluestem pastures